Internal Iliac Aneurysm Causing Hydroureteronephrosis - Tawfeeq Sangey; Sibtain Moledina (Case Reports in Radiology)
A 63-year-old presented with right lumbar pain and increased frequency of urination. Imaging revealed right internal iliac artery aneurysm causing hydroureteronephrosis and compressing the urinary bladder.